Antioxidant Properties of Alpha-Lipoic (Thioctic) Acid Treatment on Renal and Heart Parenchyma in a Rat Model of Hypertension - Ilenia Martinelli; Daniele Tomassoni; Proshanta Roy; Lorenzo Di Cesare Mannelli; Francesco Amenta; Seyed Khosrow Tayebati (MDPI AG, 2021)
Renal and cardiac impairments are frequent events in the presence of hypertension. Organ damage is mainly linked to oxidative stress due to high blood pressure and may be reduced by antioxidant supplementation. Alpha-lipoic acid (ALA) is one of most effective antioxidants. It is widely used as a nutritional supplement in a racemic mixture (+/-), even though the (+)-enantiomer is biologically active. This study was designed to investigate the effect of treatment with (+/-)-ALA and its enantiomers on renal and heart parenchyma in spontaneously hypertensive rats (SHR), using immunochemical and immunohistochemical techniques. The results confirmed that the oxidative mechanisms of organ alterations, due to hypertension, and characterized by glomerular and tubular lesions, left ventricular hypertrophy, and fibrosis but not by apoptosis were accompanied by proteins' and nucleic acids' oxidation. We found greater effectiveness of (+)-ALA compared to (+/−)-ALA in reducing oxidative stress, cardiac and renal damages in SHR. To conclude, these data propose (+)-ALA as one of the more appropriate antioxidant molecules to prevent renal and cardiac alterations associated with hypertension.